Status of trace elements zinc, copper, and selenium in transfusion dependent beta thalassemic Indian children: a cross sectional study - Choudhary, Babulal; Singh, Anurag; Goyal, Vishnu K.; Sharma, Pramod; Totetja, G. S.; Payal, Vikas; Gonmei, Zaozianlungliu (International Journal of Contemporary Pediatrics, 2019)
Background: Maintenance of normal levels of copper, selenium, and zinc play an important part in lessening the morbidities associated with thalassemia major. Levels of these elements have been found to be altered in this chronic transfusion dependent disease from all over the world, but with widely variable results. Besides repeated blood transfusions and use of chelating agents, their levels in thalassemics are affected by genetic and dietary factors also, compelling us to undertake this study in our population. The objectives of this study were assessment of serum levels of zinc, copper and selenium in transfusion dependent beta thalassemics. Methods: Cross sectional descriptive study conducted at Thalassemia Day-care Centre of a teaching hospital. Total 64 transfusion dependent thalassemics in the age group 3-18 years were subjected to serum levels of zinc, copper and selenium by inductively coupled plasma mass spectrometry technique. Results: Four (6.25%) had hypozincemia, 15 (23.43%) hypocupremia and one (1.565%) had hypercupremia. Two (3.12%) had higher selenium levels (>190 µgm/l). Conclusions: In contrast to previous studies, hypocupremia has been found to be more prevalent than hypozincemia and hyposelenemia in our population.